PENGEMBANGAN INSTRUMEN PENILAIAN PRAKTIK KERJA INDUSTRI PAKET KEAHLIAN TEKNIK SEPEDA MOTOR - Azmil, Azmil (2014)
The background to the research is the industries' assessment of students of Motorcycle Technical expertise package conducting their industrial practicum without any assessment instrument. Such an assessment is difficult to be taken for its accountability and tends to be subjective. Hence, the research aims to produce assessment instruments for industrial practicum in Motorcycle Technical expertise package that can accommodate schools' and industries' standards, and ones that are valid, reliable, and practical. The research employed Research and Development (R & D) method, initiated with a preliminary study, continued by the stages of instrument development and instrument testing. The industrial practicum assessment instruments developed here consist of an assessment instrument for technical aspects to assess students' abilities in completing a job and an assessment instrument for non-technical aspects to assess students' behavior/attitude during the industrial practicum in the work world. After getting validated by a team of experts (expert judgment), the instruments were tested to assessors/observers from the industries and students of motorcycle engineering conducting their industrial practicum. Instrument testing was carried out twice in the industries and in the school. The conclusion of the test of assessment instruments for industrial practicum in Motorcycle Technical expertise package is that all items are declared to be valid, and the reliability among assessors shows that the instrument is reliable with a very high criterion. The comments from assessors/observers on the practicability of the assessment instrument for industrial practicum in Motorcycle Technical expertise package are also positive in general